Influencia de los problemas personales, en el desempeño académica de los estudiantes de la lección nocturna del Colegio Técnico Arenillas de la ciudad Arenillas periodo lectivo 2012-2013. - Espinoza Vaca, Luis Fernando (2012)
In this research we considered as a general objective. Determine how this affects the development of skills and cognitive skills in the process enseDurante school age student, family and school share the social function, understood as the development of skills and attitudes that are essential requirements to function in life. Whereas the factors described above, lead academic student behavior, they also receive the influence of contextual variables of indisputable relevance in the teaching-learning process aprendizaje.ñanza students in first, second and third high school in school Asaad Bucaram .